Microfluidic-enabled quantitative measurements of insulin release dynamics from single islets of Langerhans in response to 5-palmitic acid hydroxy stearic acid. Issue 18 (15th August 2018) - Bandak, Basel; Yi, Lian; Roper, Michael G.
Abstract : A microfluidic device was developed to investigate the effects of a potential anti-diabetic lipid on patterns of insulin secretion. Abstract : Proper release of insulin from pancreatic islets of Langerhans is essential for maintaining glucose homeostasis. For full efficacy, both the pattern and the amount of hormone release are critical. It is therefore important to understand how insulin levels are secreted from single islets in both a quantitative fashion and in a manner that resolves temporal dynamics. In this study, we describe a microfluidic analytical system that can both quantitatively monitor insulin secretion from single islets while simultaneously maintaining high temporal sampling to resolve dynamics of release. We have applied this system to determine the acute and chronic effects of a recently-identified lipid, 5-palmitic acid hydroxy stearic acid (5-PAHSA), which is a member of the fatty acid hydroxy fatty acid class of lipids that are upregulated in healthy individuals. Chronic incubation (48 h) with 5-PAHSA significantly increased glucose-stimulated insulin secretion (GSIS) in murine islets compared to chronic incubation without the lipid or in the presence of palmitic acid (PA). The studies were continued in human islets from both healthy donors and donors diagnosed with type 2 diabetes mellitus (T2DM). Total amounts of GSIS were not only augmented in islets that were chronically incubated with 5-PAHSA, but the dynamic insulin release profiles also improved as noted by more pronounced insulin oscillations. With this quantitative microfluidic system, we have corroborated the anti-diabetic effects of 5-PAHSA by demonstrating improved islet function after chronic incubation with this lipid via improved oscillatory dynamics along with higher basal and peak release rates.